Respon Karakter Agronomi Cabai Rawit Lokal (Capsicum Frutescens L.) terhadap Perlakuan Fitohormon sebagai Upaya Domestikasi Pemuliaan Tanaman - Maria Afnita Lelang; Meri Hersiana Mata; Yosef Arlindo Taek (Savana Cendana, 2020)
This study aims to determine the response of plants through the application of natural phytohormones and to obtain the optimal concentration and frequency of the domestication of local cayenne pepper plants on the island of Timor. This study used a factorial Completely Randomized Design (CRD) consisting of two treatment factors. The first factor is the dose of organic ZPT (D) which consists of 3 levels, namely D0 control, D1 = 20 ml/water, D2 = 30 ml/water. The second factor is the application time of ZPT (B) which consists of three levels, namely B1 = 1 week, B2 = 2 weeks, B3 = 3 weeks. The results showed that there was no interaction between the time of application of phytohormones and the dose of phytohormones for all observed parameters. However, the best environmental parameters were given by a treatment dose of 90 ml/L with an application time of 2 weeks. The best growth parameters were given by treatment 90 ml/L with a time of application of 2 weeks on plant height parameters, treatment without the best phytohormone measurements on the parameters of stem diameter, weight of seeds per plant, weight of 100 seeds, fruit weight, number of fruits per plant, while the treatment without dose The phytohormone (control) produced higher yield characters than the 45 ml/L and 90 ml/L dose of phytohormone treatment. Treatment of the 45 ml/L dose is the best phytohormone measurement that provides the best fruit length per plant and fruit diameter for the cultivation of local cayenne pepper on the island of Timor.